1988
DOI: 10.1111/j.1365-2621.1988.tb08959.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pretreatment on Functional and Nutritional Properties of Cowpea Meal

Abstract: The efficiency of decorticating cowpeas was improved by hydrating to 25%, then drying to -10% moisture. Effects of drying temperature (SO", 70°, 90", llO", and 13O'C) on functional and nutritional properties of cowpea meal were assessed. Extraction rate (yield) was unaffected by heating. Average particle size and water absorption of meal were greatest for intermediate temperatures. Starch was not gelatinized at any temperature. Reduction in protein solubility, which occurred at temperature 2 9O"C, was associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(93 citation statements)
references
References 15 publications
2
89
1
1
Order By: Relevance
“…The water absorption capacity was evaluated according to Phillips et al (1988) method. Two gram of flour was weighed into a centrifuge tube and 50 mL distilled water added.…”
Section: Functional Properties Water Absorption Capacity (Wac)mentioning
confidence: 99%
“…The water absorption capacity was evaluated according to Phillips et al (1988) method. Two gram of flour was weighed into a centrifuge tube and 50 mL distilled water added.…”
Section: Functional Properties Water Absorption Capacity (Wac)mentioning
confidence: 99%
“…Determination of functional properties of taro powder The water absorption capacity (WAC) of the powders was determined following the method described by Phillips et al (1988); the water solubility index by the method of Anderson et al (1969) and the least gelation concentration (LGC) according to the method described by Coffman and Garcia (1977). Triplicate determinations were made.…”
Section: Planting Experimentsmentioning
confidence: 99%
“…Such a high level of moisture, combined with temperature, does not create extreme conditions, but may induce protein aggregation and probably some denaturation as observed on the SEM cross-sections of bean seed cotyledons after 24-h processing (Figures 1 and 2). A strong effect of the process on the protein denaturation was observed by SHEARD et al (1986) and PHILIPS et al (1988) when the water content was higher than 20%. However, mild treatment conditions and duration had a negligible influence on the total protein content (Table 2).…”
Section: Resultsmentioning
confidence: 94%
“…Water penetration through the cotyledon structure influenced protein matrix aggregation and, at the further stage of processing, caused permanent deformations and even partial denaturation of protein, which resulted in a loose arrangement of some starch granules in the cotyledon cells after 24 h of this mild water treatment at 40°C (Figures 1G, 2F). It was suggested that water is the decisive factor in the protein denaturation process (SHEARD et al 1986;PHILIPS et al 1988). PILOSOF et al (1982) indicated that a greater reduction of nitrogen solubility occurred when samples were heated at a higher moisture content.…”
Section: Resultsmentioning
confidence: 99%